REDISCOVER PARADISE: ELEVATING BALI’S MARINE TOURISM THROUGH SUSTAINABLE SOLID WASTE MANAGEMENT (SSWM) - Ardiyanto, Feri; Prakasa, Gilang; Achmadi, Tri (Journal of Marine-Earth Science and Technology, 2024)
As a global tourist destination, Bali’s marine ecosystem holds significant value for the leisure industry. However, along with the enormous growth of the industry, the island also faces an imminent waste crisis. As of 2022, 1,085,507 metric tonnes of waste are produced by the island, which 18% of it or 190,726 metric tonnes of waste left unmanaged. Coupled with monsoon and wet season weather that delivers trash ashore, effective waste management holds a pivotal role to preserve the marine ecosystem of the island and its tourism industry. By conducting a qualitative descriptive method, this research proposes sustainable solid waste management (SSWM) as an attempt to combat the waste crisis on the island. This research aims to depict the feasibility – cost, and benefit – of implementing the SSWM. The findings of this research conclude that the implementation of SSWM will benefit the marine ecosystem and further sustain tourism in Bali.